Effect of long-term sprint track cycling on cyclists` balance and vestibular function - Zou, R.; Li, G.; Duan, L. (2008 International Convention on Science, Education and Medicine in Sport: Proceedings, Vol. III, 2008)
Introduction: The purpose of this paper is to investigate the effects of long-term sprint track cycling on balance and vestibular function in cyclists. Methods Twenty five subjects were divided into three groups: control group (n=10), sub-elite sprint-trained track cyclists (n=8); elite sprint-trained track cyclists (n=7). There was a significant difference (P<0.05) between the average age for the control group (20.6±0.8 years) and the sub-elite cyclists (19.8±1.0 years) when compared to the elite sprint-trained track cyclists (25.4±2.6 yrs).The training time for the sub-elite cyclists (4.5±1.7 years) in comparison with the elite cyclists (9.9±1.8 years) was also significantly different (P<0.05). Height and weight among the three groups were not significantly different (P>0.05). The Biodex dynamic balance system was used to acquire balance data with eyes opened and closed for 30 seconds; the coefficient of difficulty of the dynamic balance test was from 7 to 7. In addition, electromyography (EMG) data was collected for the right tibialis anterior and the gastrocnemius and iEMG and MF changes were monitored [1]. Results 1. With eyes opened and closed, dynamic balance of the sub-elite cyclists and the elite cyclists in comparison with the control group was significantly different (P<0.01). Dynamic balance measures of the elite cyclists were lower than the sub-elite cyclists (P<0.05). 2. With eyes opened, there were no significant differences in integration electromyography (iEMG) or median frequency (MF) of the tibialis anterior between the sub-elite cyclists and the control group (P>0.05). However, there were significant differences in iEMG and MF between the elite cyclists and the control group (P<0.05). iEMG and MF measurements of the tibialis anterior showed no significant difference between the elite cyclists and the sub-elite cyclists (P>0.05). Additionally, iEMG and MF measurements of the gastrocnemius showed no significant difference among the three groups (P>0.05). With eyes closed, iEMG and MF values of the tibialis anterior showed significant difference between the three groups (P<0.05). iEMG of the gastrocnemius also resulted in a significant difference (P<0.05)between the three groups. 3. Dynamic balance abilities correlated with vestibular function (r=0.713, P<0.05). Conclusions The study concluded that long-term sprint track cycling could improve vestibular function and increase balance in cyclists.